Manajemen Dakwah Profetik dalam Membangun Toleransi Beragama di Tengah Problematika Sosial Keagamaan Kontemporer - Nur Hamidah Pulungan; Susanti Hasibuan (IDARI: Jurnal Manajemen Dakwah, 2026)
This study aims to analyze the concept of prophetic da‘wah management in fostering religious tolerance amid contemporary socio-religious problems. The phenomena of religious intolerance, identity polarization, hate speech based on religious sentiments, and the strengthening of religious exclusivism in the digital era indicate that modern society requires a more humanistic, inclusive, and contextual approach to Islamic da‘wah. This research employs a qualitative approach using library research and a phenomenological perspective. The data were obtained through the examination of the Prophet’s hadiths, da‘wah management literature, books, scientific journals, and various studies related to religious tolerance and contemporary Islamic preaching. Data analysis was conducted using content analysis techniques to understand the relevance of prophetic values in addressing the dynamics of modern social life. The findings reveal that prophetic da‘wah management based on the Prophet’s hadiths has strong relevance in promoting social harmony and religious tolerance. The Prophet Muhammad’s da‘wah was carried out through approaches emphasizing wisdom, dialogue, compassion, moral exemplarity, and respect for social diversity. These values demonstrate that Islamic da‘wah is not merely oriented toward the transmission of religious teachings, but also toward humanization, social transformation, and the strengthening of religious moderation. This study confirms that the integration of hadith values with the concept of prophetic da‘wah management can serve as an inclusive, moderate, and adaptive model of Islamic preaching in responding to contemporary socio-religious challenges, particularly within the digital era and multicultural societies.